Fostering Elementary Students' Critical Thinking Skills Through an Ethno-STEAM E-Book: Integrating Bungurasih Local Wisdom into Digital Learning - Firda Emilia; Ganes Gunansyah; Mareta Dellarosa (LP. Ma'arif Janggan Magetan, 2026)
This study aimed to develop an Ethno-STEAM-based interactive e-book integrating Bungurasih local wisdom and to evaluate its validity, practicality, and effectiveness in improving elementary students' critical thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE model and a one-group pretest–posttest design involving 30 third-grade students. Data were collected through expert validation, questionnaires, classroom observations, and critical thinking tests. The developed e-book achieved a validity score of 91.7% and a practicality score of 92.5%, both categorized as very valid and very practical, respectively. Students' critical thinking skills improved significantly after the intervention, with an average N-Gain of 0.61, indicating a moderate level of improvement. These findings demonstrate that integrating local wisdom, interactive multimedia, and Ethno-STEAM learning creates meaningful and contextual science learning experiences. The study implies that Ethno-STEAM digital learning media can support the implementation of culturally responsive science education while fostering critical thinking and other twenty-first-century competencies in elementary schools.